A reexamination of Monstera oreophila (Araceae: Monsteroideae) and description of two new pinkish-spathed species of Monstera from Costa Rica and Panama - Cedeño Fonseca, Marco Vinicio (2021)
Monstera gentryi from Panama and M. mittermeieri from Costa Rica are newly described, illustrated and compared with M. oreophila. The differences between the novelties and similar species are presented and an amended description of M. oreophila is provided.